Efforts to Improve Discuss throwing Skills with Water Pipe Modifications in Junior High School Students - Muhsana El Cintami Lanos; Anne Ulfa; Alvian Damanik; Sulurudin Sulurudin; Pebi Jauhari (Edumaspul: Jurnal Pendidikan, 2023)
Discus throw is one of the throwing numbers in athletics besides javelin throw and shot put. In this number, especially the discus throw, there have been many amateur class events held both at the elementary school level. This is in line with the psychomotor aspects of students have not been maximized due to the lack of facilities and infrastructure and the lack of creativity of educators in delivering material at the institution. The purpose of this research with the modification of water pipes can improve the movement of discus throwing number playing skills which can later be implemented to students. So that with these modifications, the teaching and learning process is not relatively monotonous, and the learning process can run as it should. In this study, researchers used a classroom action research method with sample data of class VII students consisting of 22 members. While the instruments in this study used total sampling techniques where observation data collection and motion tests of discus throwing skills. From the results of these observations and research, results were obtained with data on the lack of cognitive and psychomotor aspects of students during the pre-cycle process before the implementation of treatment. However, as much as (54.53%) there was an increase in the provision of water pipe modification treatment in cycle I. And there was a significant increase in cycle II with a percentage (86.38%). So that the results of the study can be concluded that using water pipe modifications is very useful for trainers, especially educators in providing discus throw practice or learning in amateur classes or students